Jemaah Islamiyah Jihadist Movement in Indonesia - Yasin, Raden Cecep Lukman (UIN Maulana Malik Ibrahim Malang, 2007)
Democratic practice in the post-Soeharto era has widely opened and led to euphoria in the public life. Some social and politics activities which were previously banned are now starting to appear openly. The emergence of Islamic radical community along with their terror acts both psychological and physical which attracts people’s attention may be a cause of this openness. One of communities which is seen as the front guard of radical movement is Jemaah Islamiyah. This article explores the historical background of the aforementioned movement and its development for the last two decades. The discussion also includes the intern dispute and its metamorphosis from just being the under-ground community to be the public community. Despite so many opinions which relate the movement with the powerful Islamism influence from Mid-Eastern, this article argues that those opinions ignore the history of Islamic radical movement in the Social Politics landscape. The precise discussion about Jemaah Islamiyah shows that this community has strong local characteristics. Keran demokrasi yang terbuka lebar pasca-kejatuhan rejim Soeharto telah menciptakan euphoria dalam ruang kehidupan publik. Berbagai aktifitas sosial politik yang sebelumnya dibungkam dan disisihkan, kini mulai memadati ruang publik. Kemunculan kelompok radikal Islam yang telah banyak menyedot perhatian publik dengan aksi-aksi mereka yang bemuasa terror, psikologis maupun fisik, tidak bisa dilepaskan dari keterbukaan ini. Di antara kelompok yang dipandang sebagai garda depan gerakan radikal ini adalah Jemaah Islamiyah.Tulisan berikut berusaha menelurusi akar kemunculan gerakan tersebut dan perkembangannya sepanjang dua dekade terakhir, berikut perpecahan internal dan metamorphosis gerakan bawah tanah itu menjadi gerakan terbuka. Sementara banyak kalangan mengaitkan gerakan tersebut dengan pengaruh islamisme yang kuat dari Timur Tengah, tulisan ini menyodorkan argumentasi bahwa pandangan di atas jelas telah mengabaikan sejarah gerakan radikal Islam dalam lanskap sosial politik Indonesia. Kajian yang cermat terhadap Jemaah Islamiyah menunjukkan bahwa gerakan tersebut memiliki karakteristik lokal yang kental.